Historical forest changes in the western United States - Craig Loehle (The Forestry Chronicle, 2020)
Changes in factors such as temperature, precipitation, fire regimes, ozone, atmospheric CO2, and nitrogen deposition may have altered forest growth over the past century. Determining changes in forest growth over long intervals is complicated by constantly changing growing conditions due to tree maturation, stand self-thinning, disturbance, and other factors. Because a comprehensive review is lacking, results from publications examining forest growth trends in the western United States over the past 100 years were evaluated. Across the region, upper elevational forest ecotones have been expanding upward in many but not all locations, possibly due to warming and reduced snowpack. Across most of the region, both growth increases and decreases are localized and spatially dispersed. For the inland West, historical photography and long-term inventory data show clear densification and expansion of ponderosa pine (Pinus ponderosa) and mixed conifer forest across the region, mostly due to reduced fire incidence. However, a recent drought, probably linked to ocean cycles and exacerbated by warming, has caused a growth setback and mortality, especially in the Southwest. Forest densification due to altered fire regimes does not equate to enhanced growth per se. Aspen (Populus tremuloides) dieback has been noted due to recent drought and local conifer mortality caused by drought has also been documented in several locations. Regeneration after recent fires appears to be inadequate in many localities. Except for local increased growth at some high elevation and coastal sites and possible periodic drought effects in the Southwest, it is difficult to detect any growth trends with available data.